Migrating Scarps as a Significant Driver for Cometary Surface Evolution. Issue 22 (28th November 2019) - Birch, S. P. D.; Hayes, A. G.; Umurhan, O. M.; Tang, Y.; Vincent, J.‐B.; Oklay, N.; Bodewits, D.; Davidsson, B.; Marschall, R.; Soderblom, J. M.; Moore, J. M.; Corlies, P. M.; et al.
Abstract: Rosetta observations of 67P/Churyumov‐Gerasimenko (67P) reveal that most changes occur in the fallback‐generated smooth terrains, vast deposits of granular material blanketing the comet's northern hemisphere. These changes express themselves both morphologically and spectrally across the nucleus, yet we lack a model that describes their formation and evolution. Here we present a self‐consistent model that thoroughly explains the activity and mass loss from Hapi's smooth terrains. Our model predicts the removal of dust via reradiated solar insolation localized within depression scarps that are substantially more ice rich than previously expected. We couple our model with numerous Rosetta observations to thoroughly capture the seasonal erosion of Hapi's smooth terrains, where local scarp retreat gradually removes the uppermost dusty mantle. As sublimation‐regolith interactions occur on rocky planets, comets, icy moons, and Kuiper belt objects, our coupled model and observations provide a foundation for future understanding of the myriad of sublimation‐carved worlds. Key Points: We report the discovery of transient, migrating depressions within the smooth terrains on comet 67P Migration is via uniform scarp retreat, which removes regolith completely from the nucleus and is driven by sublimating subsurface water ice We develop a model that fully captures our own, and many previous, disparate observations, with implications for how comets seasonally erode